2012
DOI: 10.5539/emr.v1n1p15
|View full text |Cite
|
Sign up to set email alerts
|

Examining Leader-Member Exchange as a Moderator of the Relationship between Emotional Intelligence and Creativity of Software Developers

Abstract: This paper investigates how leader-member exchange (LMX) and emotional intelligence (EI) are associated with employees' creativity in high-tech firms. We develop a model that considers LMX and EI as predictors of creativity with LMX as a boundary condition for the relationship between EI and creativity. Results reveal that LMX is a strong predictor of creativity. However, EI does not directly affect creativity. More interestingly, the interaction between EI and LMX negatively influences creativity such that EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
(104 reference statements)
0
6
0
2
Order By: Relevance
“…Existing findings on gender differences in the relationship between EI and creativity are contradictory. Although some studies found high correlations between EI and creativity in samples mainly consisting of males [37,65], other studies found relatively low correlations between the constructs in majority-male samples [28,29]. Considering these inconsistencies in the findings, we cannot exclude the possibility that gender may moderate the relationship between EI and creativity.…”
Section: Gendermentioning
confidence: 83%
See 1 more Smart Citation
“…Existing findings on gender differences in the relationship between EI and creativity are contradictory. Although some studies found high correlations between EI and creativity in samples mainly consisting of males [37,65], other studies found relatively low correlations between the constructs in majority-male samples [28,29]. Considering these inconsistencies in the findings, we cannot exclude the possibility that gender may moderate the relationship between EI and creativity.…”
Section: Gendermentioning
confidence: 83%
“…The underlying logic to this argument is that EI reflects the ability to reach consensus and produce normative solutions to social and emotional situations, while creativity conversely reflects the ability to break from routines, think flexibly, and formulate unique ideas [21,22]. In line with this theoretic explanation, a number of studies have found null associations between EI and creativity [21,[23][24][25][26][27][28][29]. For instance, Ivcevic, Brackett, and Mayer [21] examined the relationships between EI, creativity, and emotional creativity and, while they uncovered positive associations between emotional creativity and both self-reported and performance-based creativity measures, they did not find any significant associations between EI and creativity measures.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange quality. We used a version of Scandura and Graen's (1984) exchange quality scale that was adapted to have Likert-style anchors instead of idiosyncratic anchors (Lee, Scandura, Kim, Joshi, & Lee, 2012;Liden, Wayne, & Stillwell, 1993;Tekleab & Taylor, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The study adapted six items from Lee, Scandura, Kim, Joshi, and Lee (2012) to measure LMX. Sample items include "My Leader recognizes my potential well enough," and "I can depend on my supervisor at his expense when I really need it".…”
Section: Leader-member Exchangementioning
confidence: 99%